2009
DOI: 10.1099/jmm.0.004416-0
|View full text |Cite
|
Sign up to set email alerts
|

Iron-binding compounds impair Pseudomonas aeruginosa biofilm formation, especially under anaerobic conditions

Abstract: The success of Pseudomonas aeruginosa in cystic fibrosis (CF) and other chronic infections is largely attributed to its ability to grow in antibiotic-resistant biofilm communities. This study investigated the effects of limiting iron levels as a strategy for preventing/disrupting P. aeruginosa biofilms. A range of synthetic and naturally occurring iron-chelating agents were examined. Biofilm development by P. aeruginosa strain PAO1 and CF sputum isolates from chronically infected individuals was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 33 publications
(38 reference statements)
8
81
0
3
Order By: Relevance
“…Interestingly, the basal half of the biofilm layer appeared to remain unaffected by nitroxoline. Similar results were previously reported by O'May et al, who demonstrated a substantial mass but not a surface reduction by exposure of mature PAO1 biofilms to high dosages of the iron chelator 2,29-dipyridyl (about a twothird decrease in thickness at 2,500 M) (19).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Interestingly, the basal half of the biofilm layer appeared to remain unaffected by nitroxoline. Similar results were previously reported by O'May et al, who demonstrated a substantial mass but not a surface reduction by exposure of mature PAO1 biofilms to high dosages of the iron chelator 2,29-dipyridyl (about a twothird decrease in thickness at 2,500 M) (19).…”
supporting
confidence: 80%
“…Its activity is comparable to that reported for EDTA (1,19), but it is orally applicable, less toxic, and the antibiofilm effect was obtained at concentrations that are in the range achieved in vivo during oral nitroxoline treatment (plasma peak levels of approximately 6 mg/liter and persistent urine levels around 300 mg/liter) (2). In contrast to lactoferrin and the related egg white-derived conalbumin, it is a synthetic, relatively cheap compound, without additional immunomodulating functions and far lesser allergenic potential.…”
Section: Figmentioning
confidence: 52%
See 1 more Smart Citation
“…The importance of biofilm formation in the resistance to antimicrobial peptides and antibiotic therapy has been well established, and it contributes to persistence in the host (31,57,58). In addition, biofilm formation is influenced by host microenvironments that are limited in available iron, which is particularly important as the host sequesters free iron as a means to limit bacterial growth (59)(60)(61)(62)(63)(64)(65)(66)(67). We have demonstrated that transient restriction of heme iron enhances biofilm structural complexity and peak height in wild-type NTHI (B. R. Szelestey and K. M. Mason, unpublished observations).…”
Section: Resultsmentioning
confidence: 99%
“…The latter is surprising in relation to previous reports of inhibition and even disruption of Pseudomonas biofilms by lactoferrin (Singh et al 2002, Kamiya et al 2012). The anti-biofilm effect of lactoferrin was apparently not simply due to iron removal since increasing concentrations of iron in the presence of lactoferrin increased its anti-biofilm activity (O'May et al 2009). …”
Section: Iron Sources and Biofilmmentioning
confidence: 99%